Obesity : cultural and biocultural perspectives - Brewis, Alexandra (Studies in medical anthropology., 2011)
"In a world filled with more people who are overweight than underweight, public health and medical perspectives paint obesity as a catastrophic epidemic that threatens to overwhelm health systems and undermine life expectancies globally. In many societies, being obese creates profound personal suffering because it is so culturally stigmatized. yet despite loud messages about the health and social costs of obesity, weight gain is a seemingly universal aspect of the modern human condition. Grounded in a holistic anthropological approach and using a range of ethnographic and ecological case studies, 'Obesity' shows that the human tendency to become and stay fat makes perfect sense in terms of evolved human inclinations and the physical and social realities of modern life. Drawing on her own fieldwork in the rural United States, Mexico, and the Pacific Islands, the author addresses such critical questions as why obesity is defined as a problem and why some groups are more at risk than others. She suggests innovative ways in which anthropology and other social sciences can use community-based research to address the serious public health and social justice concerns provoked by the global spread of obesity"--Provided by publisher.